MnO2 Electrocatalysts Coordinating Alcohol Oxidation for Ultra‐Durable Hydrogen and Chemical Productions in Acidic Solutions. Issue 39 (18th August 2021) - Li, Yan; Wei, Xinfa; Han, Shuhe; Chen, Lisong; Shi, Jianlin
Abstract: Electrocatalytic hydrogen production under acidic conditions is of great importance for industrialization in comparison to that in alkaline media, which, unfortunately, still remains challenging due to the lack of earth‐abundant, cost‐effective and highly active anodic electrocatalysts that can be used durably under strongly acidic conditions. Here we report an unexpected finding that manganese oxide, a kind of common non‐noble catalysts easily soluble in acidic solutions, can be applied as a highly efficient and extremely durable anodic electrocatalyst for hydrogen production from an acidic aqueous solution of alcohols. Particularly in a glycerol solution, a potential of as low as 1.36 V (vs. RHE) is needed at 10 mA cm −2, which is 270 mV lower than that of oxygen evolution reaction (OER), to oxidize glycerol into value‐added chemicals such as formic acid, without oxygen production. To our surprise, the manganese oxide exhibits extremely high stability for electrocatalytic hydrogen production in coupling with glycerol oxidation for longer than 865 hours compared to shorter than 10 h for OER. Moreover, the effect of the addition of glycerol on the electrochemical durability has been probed via in situ Raman spectroscopic analysis and density functional theory (DFT) calculations. This work demonstrates that acid‐unstable metal oxide electrocatalysts can be used robustly in acidic media under the presence of certain substances for electrochemical purposes, such as hydrogen production. Abstract : This work reports a strategy of using a low‐cost acidic aqueous solution of alcohols for efficient hydrogen/chemical co‐production. The as‐prepared non‐precious metal MnO2 /carbon paper electrocatalyst in combination with alcohol oxidation demonstrates a significantly decreased total energy input for hydrogen production and ultra‐high durability in acidic electrolytes.